Intuitionistic Complex Fuzzy Hv -subgroups - Yavuz, Sanem; Onar, Serkan; Ersoy, Bayram Ali; Davvaz, Bijan; Hila, Kostaq (OLD CITY PUBLISHING INC, 2023)
In this paper, we deal with the algebraic structure of subhypergroups (H-v -subgroups) in terms of intuitionistic complex fuzzy set theory. The notion of intuitionistic complex fuzzy subhypergroups (or H-v - subgroups) is introduced, characterizations and algebraic properties of them are investigated. Additionally, intuitionistic complex anti-fuzzy subhypergroups (or H-v-subgroups) are introduced and their properties are provided. Finally, some fundamental results and transitions between two notions are given. Several examples are provided to illustrate the results.
Keywords: H-v -subgroup; intuitionistic fuzzy set; intuitionistic complex fuzzy set; intuitionistic complex fuzzy subhypergroup; intuitionistic complex anti-fuzzy subhypergroup; Computer Science; Science & Technology - Other Topics